The Evaluation of Socialization Policy and Voter Education on the Election of Regional Head in Palu City in 2020 - Idrus, Idrus; Cante, Slamet Riady; Waris, Irwan (Department of Public Administration, 2025)
This study aims to evaluate the socialization and voter education policy in Palu City by referring to the case of the Palu City regional head election held in 2020. The method used in this study is qualitative with a case study approach. Qualitative research is research where a researcher is placed as a key instrument in a study, data collection is carried out by combining and analyzing data that is inductive. While a case study is a form of in-depth research on an aspect of the social environment including the humans in it. The results of this study show that the Decision of the Palu City General Election Commission Number: 98A / PP.06.2-KPT / 7271 / KPU-KOT / X / 2019 which is the basis for conducting socialization and voter education in the 2020 regional elections has not been running well, which can be seen from the six aspects of policy evaluation, none of which are as expected. The main cause of all aspects of policy evaluation not being met was due to Covid-19, the apathy shown by the community, the mayoral and deputy mayoral candidates who partly did not conduct socialization and voter education, as well as budget and HR problems from parties involved in the 2020 regional elections. This needs to be anticipated by the Palu City KPU in the upcoming regional elections, so that these problems do not happen again in the future and also to increase community participation in exercising their voting rights.